Food Movements, Resistance, and new digital repertoires in (post-)pandemic times - Zentgraf, Lea Loretta; Kalix Garcia, Thalita (The International Journal of Sociology of Agriculture and Food, 2023)
While the Covid-19 pandemic demonstrated the vulnerability of the global food system, new resilient repertoires of collective action also showed how to overcome the multiple dimensions of this crisis. Food movements played an important role in creating innovative alternatives for a more just food system. In Germany, the pandemic affected and continues to affect agri-food relations. This article argues that digital communication was an important tool to connect people for purposes beyond sharing food and supporting food-related needs. Social media became a virtual platform for social mobilisation and innovation around food alternatives during and in a (post-) pandemic world. Two relevant actors in the German food mobilisation were the protest campaign Wir haben es satt! and the food movement Slow Food Germany. The work presented here is based on digital ethnographies and an analysis of documents from the period 2020-2022. The analysis focuses on how these two movements dealt with the crisis scenario, in relation to three classic levels of protest and social movement research: (1) actor level; (2) action level; and (3) transformation level. The comparison shows that both movements developed innovative digital and hybrid repertoires of collective action, and fostered coalitions between actors fighting for a socio-ecological transformation of the food system.